Relationships Between Community-Based Processes for Research Ethics Review and Institution-Based IRBs: A National Study - Shore, Nancy; Drew, Elaine; Brazauskas, Ruta; Seifer, Sarena D. (Journal of empirical research on human research ethics, 2011)
community groups are implementing research ethics review processes to determine whether and how research is conducted in their communities. We report on a survey of 109 of these community-based review processes about their relationships with institution based research ethics boards (I-REBs). Ninety-two percent reported that studies they review were also reviewed by an I-REB. Over half characterized their relationship with I-REBs positively. Those with positive relationships were significantly more likely to communicate with the involved I-REBs. Challenges when working with I-REBs included delays, communication problems, and lack of I-REB understanding of community-based participatory research. Strengthening relationships between community-based review processes and I-REBs could ultimately enhance reviews of community-engaged research.